2012
DOI: 10.1001/archsurg.2012.2024
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prophylaxis and Decreased Rates of Preventable Harm With the Use of a Mandatory Computerized Clinical Decision Support Tool for Prophylaxis for Venous Thromboembolism in Trauma

Abstract: Venous thromboembolism is associated with substantial morbidity and mortality and is largely preventable. Despite this fact, appropriate prophylaxis is vastly underutilized. To improve compliance with best practice prophylaxis for VTE in hospitalized trauma patients, we implemented a mandatory computerized provider order entry-based clinical decision support tool. The system required completion of checklists of VTE risk factors and contraindications to pharmacologic prophylaxis. With this tool, we were able to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
135
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 33 publications
1
135
0
Order By: Relevance
“…139,143 • Monitoring for gender bias includes observing for errors, omissions, or deviations from established protocols, standing orders, and national guidelines in our own setting as well as upon receipt of patients from emergency medical services or other facilities.…”
Section: An Unanticipated Breakthrough In Helping To Eliminate Gendermentioning
confidence: 99%
“…139,143 • Monitoring for gender bias includes observing for errors, omissions, or deviations from established protocols, standing orders, and national guidelines in our own setting as well as upon receipt of patients from emergency medical services or other facilities.…”
Section: An Unanticipated Breakthrough In Helping To Eliminate Gendermentioning
confidence: 99%
“…Adult critical care Diagnostic DXplain [28] Mortality and length of stay prediction [9,29] Alert and reminder Ventilator induced lung injury [84] Blood pressure variability while on vasopressors [32] Adverse drug reactions [19] Drug induced thrombocytopenia [30] Epidural hematoma with neuraxial anesthesia [31] Protocol/procedure Acute respiratory distress syndrome [33][34][35] Sepsis [21] VTE prophylaxis and events in trauma patients [37] VTE prophylaxis [38,39] Tidal volume during mechanical ventilation [36] Management…”
Section: Type Of Support Tool Example or Subjectmentioning
confidence: 99%
“…In the prospective cohort study by Bertsche et al [19] , implementation of a CDS program showed significant decreases in drugdrug interactions and in adverse events related to drugdrug interactions, including prolonged QT interval and hypokalemia. Additionally, CDS improves adherence to protocols for mechanical ventilation [33][34][35][36] , sepsis [21] , and venous thromboembolism prevention [37][38][39] , and can improve patient care. Such protocol use in critical care standardizes treatments of common physiologic states and is often central to quality improvement efforts in the ICU [40] .…”
Section: Type Of Support Tool Example or Subjectmentioning
confidence: 99%
“…4,5 DSTs often improve adherence to published guidelines and in many instances improve clinical outcomes, although this has not been universally true. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, most research on clinical decision support has focused upon patient management after initial assessment and diagnosis or through mandatory alerts for providers, such as reminders for intraoperative antibiotic prophylaxis, postoperative nausea and vomiting prophylaxis, or proper use of alarms for separate from cardiopulmonary bypass. [26][27][28][29][30][31][32][33][34] In contrast, the use of DSTs for patient assessment/diagnosis and the subsequent application of evidence-based protocols has yet to be rigorously tested.…”
Section: Introductionmentioning
confidence: 99%